PERSEPSI GURU TENTANGPUNISHMENT DAN IMPLEMENTASINYA DALAM PEMBELAJARAN DI MADRASAH IBTIDAIYAH KECAMATAN MEDAN TEMBUNG - Anri Naldi, Wahyudin Nur Nasution, Syaukani (Pascasarjana UIN Sumatera Utara, 2018)
ABSTRACT: This research aims to analyze: 1) How is the teacher’s perception about punishment inelementary school of Medan Tembung district? and 2) How is punishment implementation in learningconducted by a teacher in elementary school of Medan Tembung district? This research uses qualitativemethod, with use science approach to the interpretation of data obtained through interviews, observationand documentation. The results showed that: 1) Teacher’s perception of punishment is a punishment thateducates students who have a deterrent effect because they have committed a violation, the purpose ofwhich is to improve behavior, personality, character and discipline. And 2) There are two implementationsof giving the punishment: First, it is carried out in general in accordance with the regulations in theelementary school of Medan Tembung district. Second, it is carried out specifically by the teacher in thelearning process at Islamic elementary school in Medan Tembung district. Giving the punishment by teacherhas been implemented in the learning process and activities outside of learning hours with the purposefunction and basics of giving punishment and use a strategy of combining punishment methods andtechnic in the learning process in the Islamin elementary school at Medan Tembung district.Penelitian ini bertujuan untuk menganalisis: 1) Bagaimanakah persepsi guru tentang punishment diMadrasah Ibtidaiyah di Kecamatan Medan Tembung? Dan 2) Bagaimanakah implementasiPunishmentdalam pembelajaran yang dilakukan guru di Madrasah Ibtidaiyah di Kecamatan Medan Tembung? Penelitianini merupakan penelitian kualitatif dengan pendekatan fenomologi.Teknik penarikan sampling yang digunakanadalahpurposive sampling. Hasil penelitian menunjukkan bahwa: 1) Persepsi guru tentangpunishmentadalah hukuman yang mendidik yang memberikan efek jera kepada siswa karena telah melakukan pelanggaran,yang tujuannya untuk memperbaiki tingkah laku, kepribadian, akhlak dan kedisiblinan. 2) Implementasipemberianpunishment yang dilakukan ada dua: Pertama, dilakukan secara umum yaitu sesuai denganperaturan di Madrasah Ibtidaiyah Kecamatan Medan Tembung. Kedua, dilakukan secara khusus olehguru dalam proses pembelajaran di Madrasah Ibtidaiyah di Kecamatan Medan Tembung. Pemberianpunishment yang dilakukan guru telah di implementasikan dalam proses pembelajaran dan kegiatandiluar jam pembelajaran dengan tujuan, fungsi dan dasar-dasar pemberianpunishment, serta menggunakanstrategi penggabungan antara metode dan teknikpunishment dalam proses pembelajaran di MadrasahIbtidaiyah di Kecamatan Medan Tembung.Kata Kunci:Persepsi, Punishment dan Implementasi